Product Packaging and Consumer Purchase Decision: A Study of FMCG in Osogbo, Nigeria (UNIZIK Journal of Marketing, 2024)
In the 21st century marketers have adopted packaging as a marketing tool to attract consumers to increase sales volume and profitability of the organisation. The study investigated the influences of product packaging on consumer purchase decision of fast-moving consumer goods in Osogbo, Nigeria. The attributes of product packaging used in the study include package design, package shape, and package color. Primary data was collected using questionnaire as part of a survey study. Multiple regression analysis was used to test the hypotheses at the 0.05 level of confidence. Descriptive and inferential statistics were employed to facilitate data analyses. The population of the study is infinite (Unknown), Krejcie and Morgan sample size determination table posited that when population of a given study is above 75,000, a sample size of 382 can be used as such the sample size of the study taken was 382 respondents.  Findings revealed that (R=.301, R2 =.295; p
Keywords: Product packaging; consumer purchase decision; package design; package shape; package color